Reinventing functional finance : transformational growth and full employment - Forstater, Mathew, 1961-; Nell, Edward J. (Northhampton, MA : Edward Elgar Pub., 2003)
This ambitious book seeks both to revive and revise the idea of 'functional finance'. Followers of this doctrine believe that government budgets should concentrate solely on their macroeconomic impact on the economy, rather than reflecting a concern for sound finance and budgetary discipline. Reinventing Functional Finance examines the origins of this idea and then considers it in a modern context. The authors explore the concept of NAIRU and argue that modern economies can operate at the level of full employment without provoking unmanageable inflation. They also contend that budget deficits do not have the deleterious effects commonly ascribed to them; the belief that they do rests on a misunderstanding of modern money.
Includes index.
Papers presented at a conference held in the Spring of 1998 at the New School for Social Research.
rpm 02/05/13
Loans
Keywords: Monetary policy -- Congresses; Inflation (Finance) -- Congresses; Full employment policies -- Congresses; Fiscal policy -- Congresses